Strangers to neighbours : refugee sponsorship in context - Labman, Shauna, 1977-; Cameron, Geoffrey (McGill-Queen's refugee and forced migration studies ;, 2020)
"As a leading country in global refugee resettlement, Canada operates a unique program that allows private groups and individuals to sponsor refugees. This innovative approach has received growing international attention, but there remains a need for a more expansive understanding of the sponsorship framework and its potential implications within Canada and across the world. Strangers to Neighbours explains the origins and development of refugee sponsorship, paying particular attention to the unintended consequences and ethical dilemmas it produces for refugee policy. The contributors to this collection draw upon law, social science, and philosophy to bring a more robust and objective perspective of Canada's historical experience with sponsorship into wider conversations about the refugee crisis and resettlement. Together, they present recent cases that exemplify how the model has been applied and how it functions, while also analyzing the challenges that emerge in host-sponsor relations. This volume further examines how sponsorship has been implemented differently in countries such as the United States and Australia. The first dedicated study of refugee sponsorship policy, Strangers to Neighbours assembles leading scholars from a range of disciplines to consider whether Canada's system is indeed a sustainable model for the world."--